2006
DOI: 10.1002/jnr.20739
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial involvement in nitric oxide‐induced cellular death in cortical neurons in culture

Abstract: Nitric oxide (NO) is an unstable molecule with physiological and pathological properties. In brain, NO acts as a modulator of neurotransmission as well as a protector against neuronal death from several death stimuli. However, beside this protector effect, high NO concentrations produce neuronal death by a mechanism in which the caspase pathway is implicated. In this work, we demonstrate that in cortical neurons the NO toxicity is mediated by mitochondrial dysfunction. SNAP, an NO donor, induces apoptosis in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
36
0

Year Published

2007
2007
2011
2011

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(37 citation statements)
references
References 36 publications
1
36
0
Order By: Relevance
“…Brain neurons were obtained as described in [25]. Isolated neurons were suspended in EMEM medium containing 0.3 g/l glutamine, 3 g/l glucose, 10% FCS, 100 U/ml penicillin and 100 µg/ml streptomycin.…”
Section: Cell Isolation and Culturementioning
confidence: 99%
See 3 more Smart Citations
“…Brain neurons were obtained as described in [25]. Isolated neurons were suspended in EMEM medium containing 0.3 g/l glutamine, 3 g/l glucose, 10% FCS, 100 U/ml penicillin and 100 µg/ml streptomycin.…”
Section: Cell Isolation and Culturementioning
confidence: 99%
“…Cells were used after 7 days of culture. Cell purity was checked by both, cells staining with cresyl violet to identify neurons, and immunocytochemistry with the specific anti-GFAP antibody [25] to identify glial cells. Under these conditions, the glial cell number in the cultures was of 8.3 ± 3.6% of the total cell population (neurons + glial cells).…”
Section: Cell Isolation and Culturementioning
confidence: 99%
See 2 more Smart Citations
“…Studies have demonstrated both neuroprotective [29][30][31] and neurotoxic [32][33][34] effects of NO. Furthermore, in addition to the direct effects of NO on cell survival, it has been established that within cells, NO interacts with superoxide to form peroxynitrite.…”
mentioning
confidence: 99%